Preparation method of graphite porous carbon material with high specific surface area

By mixing Fe@Cu-BTC composite with a carbon source, centrifugation, high-temperature carbonization and activation treatment, graphite porous carbon material with a specific surface area of ​​up to 2720m2/g was prepared, which solved the reduction in the adsorption capacity of porous carbon materials in humid environments. Problem, significantly improving adsorption capacity and cycle life.

CN119461356APending Publication Date: 2025-02-18GUANGDONG IND TECHN COLLEGE
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411671701.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The adsorption capacity of existing porous carbon materials is reduced in humid environments, making it difficult to effectively remove organic pollutants.

Method used

By mixing the Fe@Cu-BTC composite with a carbon source, centrifugation, high-temperature carbonization and activation treatment, graphite porous carbon material with a specific surface area of ​​up to 2720m2/g is produced, reducing the competitive effect between water molecules and gas molecules.

Benefits of technology

It significantly improves the adsorption capacity of porous carbon materials, enhances the adsorption capacity of gas molecules, and extends the circulation life of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119461356A_ABST
    Figure CN119461356A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a graphite porous carbon material with a high specific surface area, and belongs to the technical field of porous carbon material preparation. The preparation method comprises the following steps: step (1), dispersing a Fe-coated Cu-BTC composite material and a carbon source in a solvent, and then sequentially performing centrifugation, high-temperature carbonization and activation treatment to obtain an activated product; and (2) sequentially carrying out impurity removal and drying treatment on the activated product prepared in the step (1) to prepare the graphite porous carbon material with high specific surface area. The preparation method comprises the following steps: mixing a Fe-coated Cu-BTC composite material with a carbon source, and carrying out centrifugation, high-temperature carbonization and activation treatment to prepare the graphite porous carbon material with the specific surface area as high as 2720m < 2 > / g.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of porous carbon material preparation, and in particular to a method for preparing a high specific surface area graphite porous carbon material. Background Art

[0002] Metal Organic Frameworks (MOFs) are new porous materials formed by the coordination of metal ions with organic ligands. They have the characteristics of good surface functionalization, high specific surface area and porosity, high adsorption capacity, easy regeneration and structural tunability. The excellent performance of MOFs has made them rapidly develop into an important environmental purification material. In recent years, the preparation of MOFs-derived porous carbons has attracted more and more attention. The reasons are as follows: (1) Under appropriate treatment conditions, the obtained MOFs-derived porous carbon materials can well maintain the unique morphology of MOFs; (2) MOFs-derived porous carbon materials have various advantages derived from their templates, such as high porosity, ultra-high surface area and adjustable pore size; (3) MOFs-derived porous carbon materials can overcome the instability of MOFs and achieve a longer cycle life. Therefore, MOFs-derived porous carbon materials show good performance in the fields of catalysis, gas storage and separation, adsorption, and energy storage and conversion. In particular, MOFs-derived porous carbon materials can be used to remove organic pollutants.

[0003] However, the main problem faced in applying MOFs-derived porous carbon materials to the actual treatment of organic pollutants is that the surface of MOFs-derived materials generally contains certain hydrophilic groups (oxygen-containing groups), which are easy to combine with water molecules in the form of hydrogen bonds in a humid environment, and their adsorption capacity is greatly reduced due to the strong competitive adsorption of water molecules. Increasing the degree of graphitization of porous carbon will lead to a decrease in the relative content of surface hydrophilic groups (such as hydroxyl groups, carboxyl groups, etc.), because the graphitization process tends to form a more regular and hydrophobic carbon layer structure. This change in turn significantly improves the surface hydrophobicity of porous carbon, thereby effectively reducing the competitive effect between water molecules and gas molecules in the adsorption process, and greatly enhancing the adsorption capacity of porous carbon for gas molecules. Therefore, it is of great significance to synthesize new graphitized carbon materials with high specific surface area. Summary of the invention

[0004] In view of this, in order to solve the technical problem of low adsorption capacity of porous carbon materials in the prior art, the present invention provides a method for preparing a graphite porous carbon material with a high specific surface area, wherein the Fe@Cu-BTC composite material is mixed with a carbon source, and then subjected to centrifugation, high-temperature carbonization and activation treatment to obtain a graphite porous carbon material with a specific surface area of ​​up to 2720 m 2 / g of graphite porous carbon material.

[0005] To achieve the above object, the present invention provides the following technical solutions:

[0006] A method for preparing a high specific surface area graphite porous carbon material comprises the following steps:

[0007] Step (1), dispersing the Fe@Cu-BTC composite material and the carbon source in a solvent, and then sequentially subjecting the mixture to centrifugation, high-temperature carbonization and activation treatment to obtain an activated product;

[0008] Preferably, the carbon source is glucose;

[0009] Step (2), after the activated product obtained in step (1) is subjected to impurity removal and drying treatment in sequence, a high specific surface area graphite porous carbon material can be obtained.

[0010] Preferably, the preparation method of the Fe@Cu-BTC composite material comprises the following steps:

[0011] The mixture of Cu-BTC and iron source is added to deionized water for ball milling to obtain solid powder; the solid powder is purified and dried to obtain Fe@Cu-BTC composite material;

[0012] Preferably, the iron source is ferric acetate.

[0013] Preferably, the mass ratio of the Cu-BTC to the iron source is (3-8):1.

[0014] Preferably, the ball milling speed is 900-1200 r / min, and the ball milling time is 30-90 min.

[0015] Preferably, the amount of deionized water added is 0.5 to 1.5 ml of deionized water per gram of reaction raw material.

[0016] Preferably, in step (1), the mass ratio of the Fe@Cu-BTC composite material to the carbon source is 1:1-3.

[0017] Preferably, in step (1), the high temperature carbonization is carried out by heating the temperature to 500-900° C. at a heating rate of 5° C. / min and maintaining the temperature for 2-6 hours while continuously introducing nitrogen;

[0018] The activation treatment is that the ratio of carbonization product to activating agent is 1:6, and the temperature is raised to 600-800°C at a heating rate of 5°C / min under nitrogen protection and maintained for 1-2h;

[0019] Preferably, the activator is potassium hydroxide.

[0020] Preferably, the impurity removal in step (2) is carried out by acid washing and water washing in sequence.

[0021] Preferably, the purification is to wash the solid powder with ethanol.

[0022] Preferably, the drying temperature in step (1) and step (2) is 120-150° C., and the drying time is 8-12 h.

[0023] Preferably, the drying in step (1) and step (2) is vacuum drying.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] The present invention selects Cu-BTC to react with an iron source to synthesize a Fe@Cu-BTC composite material. The metal nodes and ligands in Cu-BTC are connected by weak coordination bonds, which determines the disadvantage of its poor stability. In the presence of water molecules, the water molecules will coordinate with the metal center of the Cu-BTC material, resulting in the breakage of the original coordination bonds of the Cu-BTC material and the destruction of the skeleton structure. Therefore, the present invention adopts an efficient, fast and environmentally friendly mechanochemical method, with water as an etchant and ferric acetate as a second metal source. Through the etching of Cu-BTC by water, the original copper ions of Cu-BTC and the coordination bonds of trimesic acid are partially broken, forming a deprotonated organic ligand, which reacts with ferric acetate again, and successfully prepares a Fe@Cu-BTC composite material loaded with an iron graphite catalyst, and then centrifugation, high-temperature carbonization (high-temperature catalytic graphite method) and activation treatment (chemical activation) are performed to obtain a specific surface area of ​​up to 2720m 2 / g of graphite porous carbon material, showing a good degree of graphitization. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 N2 adsorption-desorption isotherms of porous carbon materials prepared in the embodiments of the present invention and the comparative examples, Figure 1 In the figure, hollow represents adsorption, solid represents desorption, hollow and solid represent the same sample, and triangle, circle and diamond represent different samples.

[0027] Figure 2 The Raman spectra of the porous carbon materials prepared in the examples and comparative examples of the present invention are shown. DETAILED DESCRIPTION

[0028] Cu-BTC (copperbenzene-1,3,5-tricarboxylate) is a metal-organic framework (MOF) material formed by self-assembly of copper ions and trimesic acid, which is used to adsorb or store small molecules.

[0029] The present invention provides a method for preparing a high specific surface area graphite porous carbon material, comprising the following steps:

[0030] Step (1), dispersing the Fe@Cu-BTC composite material and the carbon source in a solvent, and then sequentially subjecting the mixture to centrifugation, high-temperature carbonization and activation treatment to obtain an activated product.

[0031] Preferably, the carbon source can be selected from conventional carbon sources in the art, and in the present invention, glucose is preferred.

[0032] In the present invention, the mass ratio of the Fe@Cu-BTC composite material to the carbon source is 1:1-3.

[0033] In the present invention, high temperature carbonization is to increase the temperature to 500-900° C. at a heating rate of 5° C. / min and maintain for 2-6 hours under continuous nitrogen flow.

[0034] In the present invention, the activation treatment is that the ratio of carbonization product to activating agent is 1:6, and the temperature is increased to 600-800° C. at a heating rate of 5° C. / min under nitrogen protection and maintained for 1-2 hours.

[0035] In the present invention, the activator is preferably an alkaline activator, more preferably potassium hydroxide.

[0036] Step (2), after the activated product obtained in step (1) is subjected to impurity removal and drying treatment in sequence, a high specific surface area graphite porous carbon material can be obtained.

[0037] In the present invention, the impurity removal in step (2) is carried out by acid washing and water washing in sequence.

[0038] In the present invention, the drying temperature in step (1) and step (2) is 120-150° C., and the drying time is 8-12 hours. The drying in step (1) and step (2) is preferably vacuum drying.

[0039] In the present invention, the preparation method of the Fe@Cu-BTC composite material comprises the following steps:

[0040] Adding a mixture of Cu-BTC and an iron source into deionized water for ball milling to obtain a solid powder; purifying the solid powder (preferably, the purification comprises washing the solid powder with ethanol) and drying to obtain a Fe@Cu-BTC composite material;

[0041] The iron source may be an iron salt or an iron oxide, etc. In the present invention, the iron source is preferably iron acetate.

[0042] In the present invention, the mass ratio of the Cu-BTC to the iron source is (3-8):1.

[0043] In the present invention, the ball milling speed is 900-1200 r / min, and the ball milling time is 30-90 min.

[0044] In the present invention, the amount of deionized water added is 0.5 to 1.5 milliliters of deionized water per gram of reaction raw material.

[0045] The technical solution of the present invention is clearly described in detail below in conjunction with specific embodiments.

[0046] Example 1

[0047] 1.29 g Cu-BTC and 0.23 g ferric acetate were placed in a stainless steel ball mill, 2 mL deionized water was added, stainless steel ball mill beads were added, and then ball milled at 1100 r / min for 60 min to obtain a solid powder; the solid powder was washed with ethanol and then vacuum dried at 120 °C for 10 h to obtain a Fe@Cu-BTC composite material.

[0048] 1.00g Fe@Cu-BTC composite material and 2.00g glucose carbon source were dispersed in 5mL ethanol, and the mixture was stirred evenly, centrifuged and placed in a tube furnace, and heated to 800℃ at 5℃ / min for 4h under nitrogen protection. KOH (carbonized sample / KOH=1:6) was added to the carbonized sample, and the mixture was placed in a tube furnace after mixing evenly, and heated to 700℃ at 5℃ / min for 1h under nitrogen protection, and then washed with 1mol / L hydrochloric acid and water, and finally dried at 150℃ in vacuum for 10h to obtain a high specific surface area graphite porous carbon material.

[0049] Example 2

[0050] 1.35 g Cu-BTC and 0.17 g ferric acetate were placed in a stainless steel ball mill, 2 mL deionized water was added, stainless steel ball mill beads were added, and then ball milled at 1100 r / min for 60 min to obtain a solid powder; the solid powder was washed with ethanol and then vacuum dried at 130 °C for 10 h to obtain a Fe@Cu-BTC composite material.

[0051] 1.0g Fe@Cu-BTC composite material and 2.0g glucose carbon source were dispersed in 5mL ethanol, stirred evenly, centrifuged and the mixture was placed in a tube furnace, heated to 700℃ at 5℃ / min under nitrogen protection for 3h. KOH (carbonized sample / KOH=1:6) was added to the carbonized sample, mixed evenly and placed in a tube furnace, heated to 800℃ at 5℃ / min under nitrogen protection for 1h, then washed with 1mol / L hydrochloric acid and water, and finally dried at 150℃ in vacuum for 8h to obtain a high specific surface area graphite porous carbon material.

[0052] Example 3

[0053] 1.35 g Cu-BTC and 0.17 g ferric acetate were placed in a stainless steel ball mill, 1 mL deionized water was added, stainless steel ball mill beads were added, and then ball milled at 1200 r / min for 30 min to obtain a solid powder; the solid powder was washed with ethanol and then vacuum dried at 130 °C for 12 h to obtain a Fe@Cu-BTC composite material.

[0054] 1.00g Fe@Cu-BTC composite material and 1.00g glucose carbon source were dispersed in 5mL ethanol, stirred evenly, centrifuged and the mixture was placed in a tube furnace, heated to 500℃ at 5℃ / min under nitrogen protection for 6h. KOH (carbonized sample / KOH=1:6) was added to the carbonized sample, mixed evenly and placed in a tube furnace, heated to 800℃ at 5℃ / min under nitrogen protection for 1h, then washed with 1mol / L hydrochloric acid and water, and finally dried at 150℃ in vacuum for 8h to obtain a high specific surface area graphite porous carbon material.

[0055] Example 4

[0056] 1.14 g Cu-BTC and 0.38 g ferric acetate were placed in a stainless steel ball mill, 2 mL deionized water was added, stainless steel ball mill beads were added, and then ball milled at 900 r / min for 90 min to obtain a solid powder; the solid powder was washed with ethanol and then vacuum dried at 150 °C for 12 h to obtain a Fe@Cu-BTC composite material.

[0057] 1.00g Fe@Cu-BTC composite material and 3.00g glucose carbon source were dispersed in 5mL ethanol, stirred evenly, centrifuged and the mixture was placed in a tube furnace, heated to 900℃ at 5℃ / min under nitrogen protection for 2h. KOH (carbonized sample / KOH=1:6) was added to the carbonized sample, mixed evenly and placed in a tube furnace, heated to 600℃ at 5℃ / min under nitrogen protection for 2h, then washed with 1mol / L hydrochloric acid and water, and finally dried at 150℃ in vacuum for 8h to obtain a high specific surface area graphite porous carbon material.

[0058] Comparative Example 1

[0059] 1.0 g of Fe@Cu-BTC composite material was directly placed in a tubular furnace, heated to 800 °C at 5 °C / min under nitrogen protection and maintained for 4 h, then washed with 1 mol / L hydrochloric acid and water, and finally dried at 150 °C in vacuum for 8 h to obtain a graphite porous carbon material.

[0060] Comparative Example 2

[0061] 1.0 g of Cu-BTC material was directly placed in a tubular furnace, and the temperature was raised to 800 °C at 5 °C / min under nitrogen protection and maintained for 4 h. It was then washed with 1 mol / L hydrochloric acid and water, and finally dried at 150 °C in vacuum for 8 h to obtain a porous carbon material.

[0062] The nitrogen adsorption isotherms of the porous carbon materials prepared in the examples and comparative examples were measured using the three-station full-function multi-purpose adsorption instrument 3Flex produced by Micromertics, Inc., USA. Figure 1 Table 1 lists the specific surface area and pore structure of these porous carbon materials.

[0063] Table 1 Specific surface area of ​​porous carbon materials prepared in Examples and Comparative Examples

[0064]

[0065] From Table 1, we can see that the BET specific surface area of ​​the original Cu-BTC is 1493 m 2 / g, while the specific surface areas of Examples 1-4 are 2720, 2480, 2658 and 2370 m 2 / g, which are higher than those of the original Cu-BTC material, and much larger than those of Comparative Examples 1 and 2, indicating that the graphite porous carbon material prepared by the method of the present invention has a larger specific surface area and a higher porosity.

[0066] The porous carbon materials prepared in the examples and comparative examples were characterized using an inVia micro-Raman spectrometer produced by Renishaw, UK. Figure 2 The high specific surface area graphite porous carbon material prepared in the embodiment of the present invention can be -1 (D peak), 1592cm -1 (G peak) and 2700cm -1 (2D peak), where the ratio of the height of the G peak to the D peak (I G / I D ) is proportional to the graphitization degree of the carbon material, and the 2D peak is a characteristic peak of the graphene structure, indicating that the prepared porous carbon material has a good degree of graphitization. In contrast, the 2D peak was not observed in the sample of Comparative Example 2, and although Comparative Example 1 showed a small 2D peak, its significance was not as good as that of the embodiment.

[0067] The above are only preferred specific embodiments of the present invention; however, the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical solutions and improved concepts of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A method for preparing a high specific surface area graphite porous carbon material, characterized in that: The steps include: Step (1), dispersing the Fe@Cu-BTC composite material and the carbon source in a solvent, and then sequentially subjecting the mixture to centrifugation, high-temperature carbonization and activation treatment to obtain an activated product; Preferably, the carbon source is glucose; Step (2), after the activated product obtained in step (1) is subjected to impurity removal and drying treatment in sequence, a high specific surface area graphite porous carbon material can be obtained.

2. The method for preparing a high specific surface area graphite porous carbon material according to claim 1, characterized in that: The preparation method of the Fe@Cu-BTC composite material comprises the following steps: The mixture of Cu-BTC and iron source is added to deionized water for ball milling to obtain solid powder; the solid powder is purified and dried to obtain Fe@Cu-BTC composite material; Preferably, the iron source is ferric acetate.

3. The method for preparing a high specific surface area graphite porous carbon material according to claim 2, characterized in that: The mass ratio of the Cu-BTC to the iron source is (3-8):

1.

4. The method for preparing a high specific surface area graphite porous carbon material according to claim 2, characterized in that: The ball mill has a rotation speed of 900 to 1200 r / min and a ball milling time of 30 to 90 min.

5. The method for preparing a high specific surface area graphite porous carbon material according to claim 2, characterized in that: The amount of deionized water added is 0.5 to 1.5 ml of deionized water per gram of reaction raw material.

6. The method for preparing a high specific surface area graphite porous carbon material according to claim 1, characterized in that: In step (1), the mass ratio of the Fe@Cu-BTC composite material to the carbon source is 1:1-3.

7. The method for preparing a high specific surface area graphite porous carbon material according to claim 1, characterized in that: In step (1), the high temperature carbonization is carried out by heating the temperature to 500-900° C. at a heating rate of 5° C. / min and maintaining the temperature for 2-6 hours while continuously introducing nitrogen; The activation treatment is that the ratio of carbonization product to activating agent is 1:6, and the temperature is raised to 600-800°C at a heating rate of 5°C / min under nitrogen protection and maintained for 1-2h; Preferably, the activator is potassium hydroxide.

8. The method for preparing a high specific surface area graphite porous carbon material according to claim 1, characterized in that: The impurity removal in step (2) is carried out by acid washing and water washing in sequence.

9. The method for preparing a high specific surface area graphite porous carbon material according to claim 2, characterized in that: The purification is to wash the solid powder with ethanol.

10. A method for preparing a high specific surface area graphite porous carbon material according to any one of claims 1 to 9, characterized in that: The drying temperature in step (1) and step (2) is 120-150° C., and the drying time is 8-12 hours. Preferably, the drying in step (1) and step (2) is vacuum drying.